Accidental delivery of a baby during a caesarean section through a vaginal incision (a laparoelytrotomy). (23rd November 2010) - Rashid, Mumtaz; Rashid, Mohammed
Abstract : A 27-year-old woman was admitted at 39 weeks' gestation for induction of labour for gestational diabetes. During artificial rupture of her membranes, cord prolapse occurred necessitating an emergency caesarean section. At closure, the incision, instead of being in the lower uterine segment, was found to be in the vagina about 1.5 cm below the anterior lip of the cervix. This was closed routinely, both mother and the baby made an uneventful recovery and at a 6 week postnatal check-up the vaginal wall was completely healed and normal.